Unions, fossil fuel workers, and the energy transition: learning from plant closures in Finland and the U.S. - Lempinen, Hanna; Parks, Virginia; Korpikoski, Anna (Taylor & Francis, 2025)
Energy-related emissions account for nearly 85 percent of global carbon dioxide emissions. Consequently, the energy sector is a primary focus of climate policies aimed at mitigating global warming, and a transition to low-carbon and net-zero energy systems and economies is at the focus of many national and international decarbonization policies. Like other economic restructuring projects, the energy transition is not a singular process but instead is unfolding as multiple interdependent processes across geographical and temporal scales. In these processes, transitions to renewable and low-carbon energy sources also translate to transitioning away from hydrocarbons and their attendant socio-economic and socio-cultural production systems. In their most tangible form, these low-carbon transitions manifest themselves in local contexts as plant-level and industry closures that – unless carefully managed – have the potential to not only upend local socioeconomic realities but also to fuel discontent against the broader societal programme of the low-carbon transition. In this article, we take a focus on two such local low-carbon transitions – the closure of coal-fired Hanasaari power plant in Helsinki, Finland and the sudden closure of the Marathon Petroleum oil refinery in Contra Costa County, California, US – as case studies of plant-level closures that reflect several experienced transition injustices. However, our analysis goes beyond merely documenting and comparing injustices across these transition contexts. Against the backdrop of literatures on radical energy justice and the role of labour unions as just transition actors, our analysis sheds light on both the interpretations of justice labour unions work to advance and different ways in which union responses in individual plant closure contexts have broadened the unions’ scope of interest and agency in just transition related broader political and societal agendas.
Keywords: fossil-fuel workers; just transition; labour (workforce); low-carbon transition; radical energy justice; trade unions